On phase separation points for one-dimensional models - Ganikhodjaev, Nasir; Rozikov, Utkir Abdulloevich (Allerton Press, Inc., 2009)
In the paper, the one-dimensional model with nearest-neighbor interactions In, n ∈ Z, and the s pin values ±1 is considered. It is known that, under some conditions on parameters of In, a phase transition occurs for this model. We define the notion of a phase separation point between two phases. We prove that the expectation value of this point is zero and its mean-square fluctuation is bounded by a constant C(β) which tends to 1/4 as β → ∞ where β = 1/T and T is the temperature.